Biostimulants in initial Growth of DiscoveryTM Bermudagrass - dos Santos, Patrick Luan Ferreira [UNESP]; Zabotto, Alessandro Reinaldo [UNESP]; da Silva, Philippe Solano Toledo [UNESP]; do Nascimento, Matheus Vinícios Leal [UNESP]; de Godoy, Leandro José Grava [UNESP]; Tavares, Armando Reis; Bôas, Roberto Lyra Villas [UNESP] (FapUNIFESP (SciELO), 2024)
The use of bacteria and seaweed extracts as biostimulants to enhance plant growth holds promise for sustainable turfgrass management. This study aimed to investigate the effects of soil application of Azospirillum brasilense (bacterium) and Ascophyllum nodosum (seaweed) extract on the initial growth of Discovery™ bermudagrass. The study was conducted using a completely randomized design with plots measuring 0.25 m2, each with a 0.5 m border. Two separate experiments were conducted, each involving four doses of biostimulants and five repetitions. The biostimulant treatments consisted of 0, 2, 4, and 6 mL L1 A. brasilense inoculant and 0, 5, 10, and 15 mL L1 A. nodosum seaweed extract. These treatments were uniformly applied to the soil at a rate of 100 mL m2, with applications at 0, 30, and 60 days after the start of the experiment. After 90 days, the parameters green color index, green cover rate, turfgrass height, and vegetation index (normalized difference), were evaluated. The results indicated that both biostimulants significantly promoted the initial growth of DiscoveryTM bermudagrass. As the doses of the biostimulants increased, there was a corresponding increase in biomass and improved development of the turfgrass. The most pronounced responses were observed with a dose of 6 mL L1 of the bacteria inoculant and 15 mL L1 of the seaweed extract. These biostimulants fostered better turf coverage, making it challenging for weeds to establish, and potentially accelerating the production of sod grass.
Uso de bioestimulantes no crescimento inicial da grama DiscoveryTM
Keywords: Ascophyllum nodosum; Azospirillum brasilense; bactérias promotoras de crescimento; Cynodon dactylon; extrato de algas marinhas; growth-promoting bacteria; seaweed extract